Nutrition for elderly individuals during the COVID-19 pandemic - Naomi Nakayama (World Nutrition Journal, 2020)
As Japan has been facing an increasingly aged society ahead of the rest of the world, much interest has been focused on interventions for treating frailty and sarcopenia to extend healthy life expectancy in recent years. The COVID-19 pandemic has led to a crisis in healthcare systems all over the world. It has had a huge impact on not only public health but also the global economy. Due to the lack of effective vaccination and pharmacological antiviral intervention, pandemic control is dependent on public health measures. These measures have basically aimed to decrease social activities and face-to-face communication, including the restriction of public gatherings and compulsory stay-at-home policies [1]. Even though these strategies are effective in controlling the pandemic, social and economic influences have obviously affected vulnerable groups of people, including elderly individuals. Therefore, it is important to enhance the effectiveness of pandemic control measures while minimizing secondary negative consequences. This article aimed to describe the importance of maintaining good nutritional and mental health for elderly individuals during the COVID-19 pandemic, with a particular focus on frailty management.